Applications and Prospects of Microfluidic Chips in Orthopaedic Diseases - Yang, Xiran; Tang, Qiangqiang; Lai, Chen; Wu, Kai; Shi, Xuetao (Frontiers in Materials, 2021)
With the advent of an ageing society, bone-related diseases such as osteoporosis have become a major human health issue, and osteolytic lesions caused by cancer bone metastasis have always had a poor prognosis. Researchers have studied the pathogenesis of these orthopaedic diseases to obtain efficacious treatments. Microfluidic chip technology is a popular technology developed in recent years. This technology can build an experimental platform for a bionic in vivo microenvironment in vitro, which has been favored by an increasing number of researchers. In this review, we will take osteoporosis and cancer bone metastasis as examples to illustrate the pathogenesis, introduce the latest progress in the research of orthopaedics-related diseases of the microfluidic model, and describe the current approaches and their limitations.